Microbiological and formaline test on the big eye tuna (Thunnus obesus Lowe, 1839) from fish auction place (TPI) and moving fish trader (PIK) in Panimbang Pandeglang Village Banten - Lia Amelia Pertiwi; Hadi Susilo; Nurullah Asep Abdilah (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
Big Eye Tuna (Thunnus obesus Lowe, 1839) is one of the fish species that can increase sources of animal protein and has high economic value in the world of trade because it is the second-largest export commodity after shrimp. The purpose of this study was to test the content of microbial and formalin contamination in the flesh of T. obesus fish from the Fish Auction Place (TPI) and Mobile Fish Trader (PIK) in Panimbang Village, Pandeglang, Banten. The research was carried out at the Regional Technical Implementation Unit (UPTD) Testing and Application of Quality of Fishery Products, Department of Marine Affairs, and Fisheries of Banten Province. This research is a descriptive laboratory study with purposive sampling. Twelve samples of T. obesus fish obtained from TPI (6 fishes) and PIK (6 fishes) were taken for 25 g of meat. The tested for microbial contamination content with Total Plate Count (TPC) using Butterfield's phosphate (BFP) media, and Plate Count Agar (PCA), Coliform-Test, and E. coli-Test using Lauryl Tryptose Broth (LTB). Brilliant Green Lactose Bile (BGLB), EC Broth and Levine's Eosin Methylene Blue (LEMB), and Formaldehyde-Test using Formaldehyde-Test Kits. The results showed that the flesh of T. obesus fish contained microbial contamination with the average values ​​of TPC, Coliform MPN, and E. coli MPN, respectively, namely 1.6 103 colony/g, 15.2 MPN/g and < 3 MPN/g ( TPI), and 1,7103 colony/g, 61.3 MPN/g and < 3 MPN/g (PIK). Therefore, fish in TPI and PIK are safe for consumption as stipulated in SNI.